2014
DOI: 10.1016/j.neuroscience.2014.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Matching of feedback inhibition with excitation ensures fidelity of information flow in the anterior piriform cortex

Abstract: Odor-evoked responses in mitral cells of the olfactory bulb are characterized by prolonged patterns of action potential (spike) activity. If downstream neurons are to respond to each spike in these patterns, the duration of the excitatory response to one spike should be limited, enabling cells to respond to subsequent spikes. To test for such mechanisms, we performed patch-clamp recordings in slices of the mouse anterior piriform cortex. Mitral cell axons in the lateral olfactory tract (LOT) were stimulated el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Previous studies used higher LOT stimulation intensities or multiple pulses that evoked spike responses in excitatory neurons and recruited recurrent inhibition from L2/3 interneurons (27,28). To investigate excitation and inhibition recruited by intracortical circuits in the absence of afferent drive, we electrically stimulated the border of L2/3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies used higher LOT stimulation intensities or multiple pulses that evoked spike responses in excitatory neurons and recruited recurrent inhibition from L2/3 interneurons (27,28). To investigate excitation and inhibition recruited by intracortical circuits in the absence of afferent drive, we electrically stimulated the border of L2/3.…”
Section: Resultsmentioning
confidence: 99%
“…There have been conflicting descriptions of the contributions of feedforward and recurrent inhibition to odor processing (3,24,27,28,32). For example, it has been suggested that feedforward inhibition is broadly tuned in vivo (3).…”
Section: Afferent Vs Intracortical Recruitment In Different Principamentioning
confidence: 99%
See 3 more Smart Citations